THE ROLE OF SUSTAINABLE AGRICULTURE ON THE GROWTH AND YIELD OF EGGPLANT - & AL-Baity, Abu-Alaees (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field experiment was carried out in the vegetable field of Horticulture Department and Landscape Gardening, College of Agriculture, Abu-Ghraib In the spring season 2014 to study the Role of Sustainable agriculture in the growth and yield of Eggplant, were studied of Two factors the first factor represent two treatment, first is shading with plastic nets (50% light) and the second without shading, each of these treatment contained three replicates and distributed randomly these eight treatments (without adding, Endospor Dry Mix, Biohealth, Amino Alexin, interacion between Endospor Dry Mix and Biohealth interaction between Endospor Dry Mix and Amino Alexin interaction between Biohealth and Amino Alexin triple interaction between Endospor Dry Mix and Biohealth and Amino Alexin and symbolized by (Control, A, B, O, AB, AO, BO and ABO). The experiment carried out within (Nested Design), and analyzed according to test least significant difference ( LSD) and at the probability level of 5%, Results showed the treatment A gavr a significant increase at height of the plant (98.5 cm), and the number of leaves (135.0 leaf.plant-1), and the dry weight of vegetative (125.8 g), and the length of the main root (51.17 cm), and the dry weight of roots (17.82 g), and the length of the fruit (11.64 cm), and the diameter of the fruit (6.40 cm), and the number of fruits (13.45 fruit), and the plant yield (2.30kg.plant-1). It excelled treatment using biostimulative ABO significantly in (leaf content of N 3.045%), and ( leaf contant P 0.684%), and (leaf content K 2.878%). The treatment of shading significantly in the plant height (97.6 cm), and the number of leaves (117.4 leaf.plant-1), and the dry weight of vegetative (108.5 g), and the length of the main root (47.54 cm) and the dry weight of the roots (12.91 g) and the length of the fruit (11.14 cm) and the fruit diameter (6.71 cm) and the weight of the fruit (169.6 g) and the number of fruits (11.21 fruit.plant-1) and the plant yield (1.91 kg.plant-1). The interaction between treatment A and shading significantly in the number of leaves (150.0 leaf.plant-1), and the dry weight of vegetative (136.7 g) and the length of the main root (53.0 cm), and the dry weight of roots (21.38 g) and the length of the fruit (12.80 cm) and the number of fruits (14.37 fruit. plant -1) and the plant yield (2.47 kg.plant-1). The interaction between the treatment AO and the shading significantly in the plant height (122.7 cm), and the length of the main root (53.00 cm) and the diameter of the fruit (7.10 cm).